Voltage‐dependent activation of Rac1 by Nav1.5 channels promotes cell migration. Issue 4 (15th October 2019) - Yang, Ming; James, Andrew D.; Suman, Rakesh; Kasprowicz, Richard; Nelson, Michaela; O'Toole, Peter J.; Brackenbury, William J.
Abstract: Ion channels can regulate the plasma membrane potential (Vm ) and cell migration as a result of altered ion flux. However, the mechanism by which Vm regulates motility remains unclear. Here, we show that the Nav 1.5 sodium channel carries persistent inward Na + current which depolarizes the resting Vm at the timescale of minutes. This Nav 1.5‐dependent Vm depolarization increases Rac1 colocalization with phosphatidylserine, to which it is anchored at the leading edge of migrating cells, promoting Rac1 activation. A genetically encoded FRET biosensor of Rac1 activation shows that depolarization‐induced Rac1 activation results in acquisition of a motile phenotype. By identifying Nav 1.5‐mediated Vm depolarization as a regulator of Rac1 activation, we link ionic and electrical signaling at the plasma membrane to small GTPase‐dependent cytoskeletal reorganization and cellular migration. We uncover a novel and unexpected mechanism for Rac1 activation, which fine tunes cell migration in response to ionic and/or electric field changes in the local microenvironment. Abstract : Ion channels can regulate the plasma membrane potential (Vm ) and cell migration as a result of altered ion flux. We show that the Nav 1.5 sodium channel depolarizes the resting Vm, promoting Rac1 activation at the leading edge of migrating cells. By identifying Nav 1.5‐mediated Vm depolarization as a regulator of Rac1 activation, we link ionic and electrical signaling at the plasma membrane to small GTPase‐dependent cytoskeletal reorganization and cellular migration.